The problematic of poverty reduction through community driven development a critical study of the Kalahi-CIDSS - Ngadima, Christel Arnaud (National College of Public Administration and Governance, University of the Philippines Diliman, 2019)
For decades many have claimed that Community Driven Development (CDD) successfully empowers local communities and reduces poverty. Even as many countries have implemented or are implementing CCD projects, yet the scientific research on the impact of this development strategy hardly offers such a clear picture. This dissertation discusses the evidence, and reviews the existing literature on the impact of the KALAHI-CIDSS on poverty reduction in the Philippines. The KALAHI-CIDSS is CDD introduced in 2002 within the Philippine developmental landscape as a flagship anti-poverty program and primarily financed through loans from the World Bank. After more than 16 years of implementation, we have no clear evidence to show that this program has reduced poverty in the poorest of poor communities. This situation is problematic and raises the fundamental questions to research: Why did the KALAHI-CIDSS project not succeed in bringing about the desired/expected outcomes?